The Role of Digital Marketing in Increasing Tourist Visits to Trekking Attractions in Bukit Lawang - Walga, Rikka Pratiwi; Sembiring, Beby Karina Fawzeea; Harahap, Hamdani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze the efforts made by tourism managers in digitalizing tourism development to increase tourist visits in Bukit Lawang and to analyze the impact of digital tourism on increasing visits to tourist attractions in Bukit Lawang. This research method is qualitative with a phenomenological approach. The data collection process is carried out through in-depth interviews and direct observation at the Bukit Lawang trekking tourist attraction. The results of the research show that the efforts made by tourism managers in digitizing tourism marketing have succeeded in increasing tourist visits in Bukit Lawang The implementation of this program has gone well.